2015
DOI: 10.1099/ijs.0.000236
|View full text |Cite
|
Sign up to set email alerts
|

Elizabethkingia endophytica sp. nov., isolated from Zea mays and emended description of Elizabethkingia anophelis Kämpfer et al. 2011

Abstract: A slightly yellow bacterial strain (JM-87 T), isolated from the stem of healthy 10 day-old sweet corn (Zea mays), was studied for its taxonomic allocation. The isolate revealed Gramstain-negative, rod-shaped cells. A comparison of the 16S rRNA gene sequence of the isolate showed 99.1, 97.8, and 97.4 % similarity to the 16S rRNA gene sequences of the type strains of Elizabethkingia anophelis, Elizabethkingia meningoseptica and Elizabethkingia miricola, respectively. The fatty acid profile of strain JM-87 T cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 31 publications
0
44
0
Order By: Relevance
“…The description is as given by Kämpfer et al (2015) with the following addition. The genomic G+C content of the type strain is 35.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The description is as given by Kämpfer et al (2015) with the following addition. The genomic G+C content of the type strain is 35.4%.…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis demonstrated that the Elizabethkingia anophelis strain identified in our study has a 100% sequence identity to Elizabethkingia anophelis which was originally isolated from the midgut of Anopheles gambiae [20]. This strain has a 99% identity to Elizabethkingia endophytica , originally isolated from sweet corn [21]. It was closely related to the Elizabethkingia genomosp .…”
Section: Resultsmentioning
confidence: 75%
“…Four species were assigned to this genus, Elizabethkingia meningoseptica (3), Elizabethkingia anophelis (4), Elizabethkingia miricola (3), and Elizabethkingia endophytica (5), with the first three considered to be medically important (6). E. meningoseptica (epithet name referring to the association of this bacterium with both meningitis and septicemia) was first described as a type species and is the best studied (2).…”
Section: Genome Announcementmentioning
confidence: 99%